Evaluation of Universitas Indonesia Library Website Using UX Questionnaire and Usability Testing - Aditia Aditia; Rahmi Rahmi; Mamlahatun Buduroh (Perpustakaan Nasional, 2024)
A good user experience supports libraries in providing search and delivery services that meet user expectations and needs. This study evaluates the user experience of the Universitas Indonesia Library (UI) website by employing the User Experience Questionnaire (UEQ) and usability testing to ascertain how well it meets user expectations and needs. Utilizing a mixed-methods approach, it gathers quantitative data from 287 respondents via UEQ and qualitative insights from usability testing involving 5 participants. The findings from the UEQ indicate generally positive user experiences across most dimensions, with the exception of Novelty, which falls below the average benchmark in terms of Attractiveness, Clarity, and Novelty. Despite the positive feedback in several areas, the overall user experience of the UI Library website is deemed inadequate, highlighting a significant need for enhancements in user experience design. The paper elaborates on design recommendations derived from both UEQ results and usability testing observations. These recommendations are intended to guide improvements in the website’s interface and functionality, ensuring it more effectively serves its academic audience. Further analysis of these recommendations is suggested to verify their appropriateness and potential impact on the user experience.